A Study of Acoustic Emission Based RA-AF Characteristics of Polypropylene Fiber-Reinforced Recycled Aggregate Concrete Under Uniaxial Compression - ZHOU, Daowen; YANG, Xin; TANG, Yu; MIAO, Yutao (Archives of Acoustics, 2024)
In order to research the acoustic emission characteristics of polypropylene fiber-reinforced recycled aggregate concrete under uniaxial load, 20 groups of test specimens with a coarse aggregate substitution rate of 25 % and 50 % are designed and fabricated to conduct the acoustic emission test under uniaxial compression, and the evolution laws of the acoustic emission b-value, the cracking modes and the acoustic emission RA-AF moving averages with time are studied. The laws of influence of the coarse aggregate substitution rate and coarse-fine polypropylene fiber on the acoustic emission b-value of RAC are discussed. The K-means clustering method is adopted for two-dimensional clustering analysis of the shear cracking and tensile cracking, and then the SVM is used to obtain the boundary between the two types of clusters. The time distribution laws of shear cracking and tensile cracking of the polypropylene fiber-reinforced recycled aggregate concrete are analyzed. The changes in the moving averages of RA and AF of RAC test specimens with time are studied, and the research indicates that as the RA value decreases, the shear cracking gradually reduces and the tensile cracking gradually increases and dominates.